10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Nonspecific low back pain is highly prevalent and disabling. Most current guidelines state that evidence is insufficient to recommend lumbar belts for this condition. OBJECTIVE: To determine whether a soft and extensible lumbar belt reduces functional disability and pain in patients with nonspecific low back pain. DESIGN, SETTING, AND PARTICIPANTS: This multicenter, open-label, randomized clinical trial was conducted at 17 medical centers across France from February 26, 2021, to March 28, 2024. Participants were adults with nonspecific low back pain lasting 1 to 6 months. Data were analyzed from August 7, 2024, to June 18, 2025. INTERVENTIONS: Patients were randomized using an interactive web response system to wear a nonrigid lumbar belt for 12 weeks in addition to usual care or to receive usual care without a device. MAIN OUTCOMES AND MEASURES: The primary outcome was the between-group difference in mean change in the Oswestry Disability Index (ODI) score from baseline to week 12. Outcomes were assessed at baseline, week 4, and week 12; pain was also reported weekly using online questionnaires. RESULTS: At total of 168 patients were randomized (mean [SD] age, 49.0 [13.7] years; 101 women [60.1%]), with 86 participants in the belt group and 82 participants in the usual care group. The primary analysis included 155 patients with at least 1 postrandomization assessment (81 patients in the belt group; 74 patients in the control group). ODI improvement from baseline to week 12 was greater in the belt group (change, -10.0 [95% CI, -13.0 to -7.0] points) than in the control group (change, -5.3 [95% CI, -8.6 to -2.1] points), with a between-group difference of -4.7 (95% CI, -8.4 to -0.9) points (P = .01). Reductions in pain at rest and during activity were also greater in the belt group, with between-group differences of -8.7 (95% CI, -16.1 to -1.3) points (P = .02) and -10.0 (95% CI, -18.3 to -1.6) points (P = .02), respectively. Over 12 weeks, medication use was lower in the belt group than in the control group (41 patients [50.6%] vs 50 patients [67.6%]; P = .03). No serious device-related adverse events occurred. CONCLUSIONS AND RELEVANCE: In this randomized clinical trial, adding a nonrigid lumbar belt to usual care resulted in improved pain and functional disability in patients with nonspecific low back pain lasting 1 to 6 months. These findings suggest that lumbar belts may be considered as a nonpharmacological option for symptom management. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04701073.